Extração da celulose da casca da banana prata (M.spp) por um método verde e avaliação da influência de água na estrutura molecular da celulose - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The silver banana peel, is a waste that causes environmental damage due to its large volume from consumption and banana farming. Because it is a rich source of cellu- lose and because of its availability, the silver banana peel was chosen to extract cellulose through a route less aggressive to the environment. Using a low concentration of NaOH (5%) solution and less reactants in proportion to the bleaching, the cellulose was extrac- ted, however, not in its entirety because through the X-ray Diffraction (XRD) analyzes, Infrared Spectroscopy (FTIR), thermogravimetry (TG) and Differential Scanning Calori- metry (DSC), the fractions of its components (hemicellulose and lignin) can be identified. Through the refinement of Le Bail method from the XRD standards, it was verified that the extracted cellulose is of the native Iα type, that is, the mercerizing and bleaching treatment did not change its native type, presenting the following cell parameters: a = 9.985 ̊A; b = 6.732 ̊A, c = 6.552 ̊A, α = 72.940, β = 116.424 e γ = 126.046. To understand the interaction of cellulose with water, the cellulose was subjected to the freeze drying process. Through the XRD data, it was verified that the freeze drying process altered the conformation of the cellulose chains, resulting in a molecular relaxation along the directions [100] and [010], resulting in increased unit cell parameters in these directions, suggesting that the removal of the water molecules by means of freeze drying directly interfered with the conformation of the cellobiosis inside the unit cell. By means of the peaks deconvolution method, it was observed that, despite the modifications observed in the XRD pattern, the percentage of crystallinity did not have a significant increase in terms of areas of diffraction peaks. Thermal analyzes pointed to the degradation of the freeze drying cellulose at 230°C, an increase of approximately 23°C in comparation to the non-freeze drying cellulose, which can be understood as an increase in the stability of the cellulose after freeze drying process. The morphology of the samples was done through Scanning Electron Microscopy (SEM). The morphology of the banana peel in natura presented irregular morphologies, and the morphology of the non-freeze drying cellulose (CNL) in comparison to the freeze drying cellulose (CL) showed no variations, both of which showed the entangled cellulose nanofibers. The average diameters of the nanofibers did not change with the freeze drying process, resulting in 11.6 nm for the CNL and 11.1 nm for the CL. We believe that this research has its relevance from the point of view of science, since it proposes a green and less aggressive method from the environmental point of view, besides serving as an alternative proposition for the recovery of one of the main biomasses of the region north, the silver banana peel.
Keywords: Silver banana peel.; Cellulose; Cellulose extraction; Freeze drying; Casca da banana prata; Celulose; Difração de raios X; Extração de celulose; Liofilização; ENGENHARIAS